(untitled) (London Journal of Research In Humanities and Social Sciences, 2023)
Considering that the insertion of language at school context is relevant to the relation established between learners and language learning, we aim in this paper to understand the effects of the process of the disciplinarization of the English language in Brazilian public schools to the learners. The devices of Discourse Analysis (Pêcheux) will constitute the theoretical and analytical support of this work, taking into account the socio-historical, and ideological, conditions in which speeches were produced. Besides, we seek an interface with the History of Linguistic Ideas, since it allows us to better understand this relationship in it social dimension, in view of its effects, especially with regard to the relationship between Brazilians and their mother tongue.